2013
DOI: 10.1371/journal.pone.0053879
|View full text |Cite
|
Sign up to set email alerts
|

Associations and Impact Factors between Living Arrangements and Functional Disability among Older Chinese Adults

Abstract: ObjectivesTo examine the association of living arrangements with functional disability among older persons and explore the mediation of impact factors on the relationship.DesignCross-sectional analysis using data from Healthy Aging study in Zhejiang Province.ParticipantsAnalyzed sample was drawn from a representative rural population of older persons in Wuyi County, Zhejiang Province, including 1542 participants aged 60 and over in the second wave of the study.MeasurementsLiving arrangements, background, funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
63
2
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 45 publications
15
63
2
11
Order By: Relevance
“…Living arrangement was associated with ADL/IADL disability in previous studies, this relationship also confirmed in this study [15]. Elderly people living alone appeared to have better functionality, and those living with other relatives/non-relatives have the highest risk of ADL/IADL disability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Living arrangement was associated with ADL/IADL disability in previous studies, this relationship also confirmed in this study [15]. Elderly people living alone appeared to have better functionality, and those living with other relatives/non-relatives have the highest risk of ADL/IADL disability.…”
Section: Discussionsupporting
confidence: 90%
“…Most of previous studies were conducted in high-income countries, but social demographic status has been found strongly associated with the prevalence of multimorbidity and disability, regardless of whether social demographic status is measured by age, race, or area-based deprivation [13, 15]. There is a lack of a better understanding of the relationship between multimorbidity and disability among Asian elderly populations, as Asian was more susceptive to ADL disability compared with other races [13].…”
Section: Introductionmentioning
confidence: 99%
“…From our data, older adults living with children at baseline reported lower cognitive function (mental status) at both baseline and follow up. Findings that living with children was associated with physical disabilities were reported in other studies [41][42][43]. This pattern may be attributed to the fact that older adults with physical or cognitive impairment tend to live with their children for support.…”
Section: Discussionsupporting
confidence: 59%
“…In a cross-sectional analysis, Wang et al [37] found that living arrangements were significantly associated with activities of daily living. They also suggested that unmarried elderly people living only with their children had significantly greater disability than those in other living arrangements.…”
Section: Discussionmentioning
confidence: 99%